Transverse momentum, rapidity, and centrality dependence of inclusive charged-particle production in √sNN = 5.02 TeV p + Pb collisions measured by the ATLAS experiment - Alconada Verzini, María Josefina (2016)
Measurements of the per-event charged-particle yield as a function of the charged-particle transverse momentum and rapidity are performed using p + Pb collision data collected by the ATLAS experiment at the LHC at a centre-of-mass energy of √sNN = 5.02 TeV. Charged particles are reconstructed over pseudorapidity |η| < 2.3 and transverse momentum between 0.1 GeV and 22 GeV in a dataset corresponding to an integrated luminosity of 1 μb−1. The results are presented in the form of charged- particle nuclear modification factors, where the p + Pb charged-particle multiplicities are compared between central and peripheral p + Pb collisions as well as to charged-particle cross sections measured in pp collisions. The p + Pb collision centrality is characterized by the total transverse energy measured in −4.9 < η < −3.1, which is in the direction of the outgoing lead beam. Three different estimations of the number of nucleons participating in the p + Pb collision are carried out using the Glauber model and two Glauber–Gribov colour-fluctuation extensions to the Glauber model. The values of the nuclear modification factors are found to vary significantly as a function of rapidity and transverse momentum. A broad peak is observed for all centralities and rapidities in the nuclear modification factors for charged- particle transverse momentum values around 3 GeV. The magnitude of the peak increases for more central collisions as well as rapidity ranges closer to the direction of the outgoing lead nucleus.